CADANGAN PREMI DENGAN METODE CANADIAN PADA ASURANSI JIWA BERJANGKA - Ike Ruliysmawati Khoirunnisa; Hasriati '; Harison ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the prospective reserve of term life insurance of the Canadian method. The method gives the extend of modified period over the entire premium payment period. Term life insurance reserve calculation is solved by determination of the single premium, annual premium, and annuity based on the assumption of constant force in advance.